ISOLASI DAN IDENTIFIKASI MOLEKULER BAKTERI ANTAGONIS TERHADAP Vibrio parahaemolyticus PATOGEN PADA UDANG Litopenaeus vannamei DARI PRODUK PROBIOTIK DAN SEDIMEN MANGROVE DI REMBANG - Bunga Fajriani; Anto Budiharjo; Sri pujiyanto (Jurnal Akademika Biologi, 2018)
Shrimp is one of the main commodities in the aquaculture industry because it has high economic value and high demand product. The Litopenaeus vannamei shrimp have the advantage of being able to grow as fast as a tiger shrimp (3 g / wk), can be grown on a wide salinity range (0.5-45 ppt), lower protein requirement (20-35%) than tiger shrimp and stylirostris shrimp. Vibrio parahaemolyticus is a normal flora in the brackish waters environment which is pathogenic to shrimp commodities as well as in humans. The use of Probiotics as additional feed in the form of microbial cells intact widely used in shrimp farming as one effort to improve the quality of the environment and supress the growth of pathogenic bacteria. One of the probiotic products used is super PS. This study aims to obtain bacterial isolate probiotic products that can suppress the growth of Vibrio parahaemolyticus bacteria. Isolation is also done on mangrove sediments as a comparable type of bacteria that can suppress the growth of pathogens. Methods used include isolation of bacterial probiotic and mangrove sediments, antagonistic test, and molecular identification with PCR methods (Polymerase Chain Reaction). The isolation result obtained by seven isolate bacteria of probiotic product and eleven isolate of mangrove sediment bacteria. One selected bacterial isolate from isolation of probiotic product that is IP 7 which able to supress the growth of Vibrio parahaemolyticus with a diameter of clear zone 10.84 mm. The results of identification using the 16S rRNA gene sequence showed that IP 7 isolate had a similarity index of 92% with Lysinibacilllus cresolivorans.Keyword : Litopenaeus vannamei, Vibrio parahaemolyticus, probiotics, antibacterial, gen 16S rRNA.